Intraoperative strategies to overcome difficulties in laparoscopic cholecystectomy for chronic calculous cholecystitis - Singh, Mohinder; Goel, Dipesh (International Surgery Journal, 2021)
Background: Surgery in chronic cholecystitis is very challenging because of inability to hold the gall bladder, dense adhesions, frozen Calot’s triangle and difficulty in applying clips. Precise and meticulous dissection is required to establish critical view of safety. There is no consensus among surgeons about appropriate intraoperative steps in difficult gall bladder (GB) surgery. The authors aim to present various intraoperative difficulties and strategies to overcome them. Methods: A prospective study of 81 patients of chronic cholecystitis was done in our institution. They were divided in two groups. Group A in which surgery could be done easily. Group B in which surgery was difficult and different intraoperative strategies were applied to overcome them. Results: Total 42 patients were included in group A and 39 patients in group B. Various difficulties encountered while performing laparoscopic cholecystectomy in group B were adhesions (53.8 %), inability to grasp the fundus of GB (15.3%), frozen Calot’s triangle (15.3%), inability to grasp the Hartmann’s pouch (12.8%) and cystic duct edema (2.5%). Conclusions: Intraoperative technique of identification of Rouviere′s sulcus first, followed by high peritoneal incision on the GB body. Subsequently blunt dissection of Calot’s triangle using gauze piece and hydro dissection by suction irrigation canula ventral to the sulcus. It created a retro gall bladder tunnel safely. It established the critical view of safety in all our cases.